Dosage of joint mobilisation for the management of rotator cuff-related shoulder pain: protocol for a scoping review - Steve Tumilty; Daniel C Ribeiro; Sizhong Wang; Cathy M Chapple; Dusty Quinn (BMJ Open)
Introduction Rotator cuff-related shoulder pain is the most common diagnosis of shoulder pain, which ranks as the third most common musculoskeletal disorder. The first-line treatment for patients with rotator cuff-related shoulder pain is physiotherapy, and joint mobilisation is widely used in conjunction with other modalities. The type and dosage of joint mobilisations could influence treatment outcomes for patients with rotator cuff-related shoulder pain, although research evidence is inconclusive.Objectives To (1) systematically search, identify and map the reported type and dosage of joint mobilisations used in previous studies for the management of patients with rotator cuff-related shoulder pain; and (2) summarise the rationale for adopting a specific joint mobilisation dosage.Methods and analysis We will follow the methodological framework outlined by Arksey and O’Malley and report the results as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guideline. Two authors will independently screen and extract data from the six databases: PubMed, Scopus, Web of Science, CINAHL, Cochrane Library and SPORTDiscus, with publication date from their inceptions to 25 August 2021. A third author will be consulted if the two authors disagree about the inclusion of any study in the review. We will summarise the results using descriptive statistics and qualitative thematic analysis.Ethics and dissemination Ethical approval is not required for this protocol. Mapping and summarising the reported type and dosage of joint mobilisations for patients with rotator cuff-related shoulder pain from previous studies will provide a foundation for further optimal selection of type and dosage of joint mobilisations for treating patients with rotator cuff-related shoulder pain. The review is part of an ongoing research that focuses on joint mobilisation for patients with rotator cuff-related shoulder pain. The results will be disseminated through presentations at academic conferences and a peer-reviewed publication.